2015
DOI: 10.1016/j.pharep.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic AMP effects and neuroprotective activities of PACAP and VIP in cultured astrocytes and neurons exposed to oxygen-glucose deprivation

Abstract: The obtained results showed that hypoxia/ischemia may trigger down-regulation of the brain AC-coupled PACAP/VIP receptors, with a consequent decrease of PACAP- and/or VIP-ergic-dependent cAMP-driven signaling. Moreover, our findings indicate that PACAP and VIP can prevent the deleterious effect of OGD on rat neuronal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Namely, it is known that VIP may stimulate the glial cells, which enhances the survivability of neuronal cells. 65 In turn, GAL is known to display trophic activity within the central and peripheral nervous system, 66 69 and the present observations demonstrate a similar activity of this toxin in the intestine. Since acetylcholine is a strong factor acting on muscular contraction, it is highly probable that a decrease in the number of VAChT-positive structures (especially in the myenteric plexus) is connected with the direct impact of BPA on intestinal muscle contraction, which has been reported in the previous studies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Namely, it is known that VIP may stimulate the glial cells, which enhances the survivability of neuronal cells. 65 In turn, GAL is known to display trophic activity within the central and peripheral nervous system, 66 69 and the present observations demonstrate a similar activity of this toxin in the intestine. Since acetylcholine is a strong factor acting on muscular contraction, it is highly probable that a decrease in the number of VAChT-positive structures (especially in the myenteric plexus) is connected with the direct impact of BPA on intestinal muscle contraction, which has been reported in the previous studies.…”
Section: Discussionsupporting
confidence: 71%
“…The participation of the majority of substances studied during the present investigation of such processes has been reported in previous studies. Namely, it is known that VIP may stimulate the glial cells, which enhances the survivability of neuronal cells . In turn, GAL is known to display trophic activity within the central and peripheral nervous system, which enhances cholinergic neuron survival and stimulates the growth of neuronal projections.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropeptide PACAP mediates neurite outgrowth and neuroprotection; however, it is not known if these events involve PAC1 receptor-induced TG2 activation (Monaghan et al, 2008;Manecka et al, 2015;Jóźwiak-Bębenista et al, 2015). TG2 can catalyse two types of transamidation, namely (i) intra-, and/or inter-molecular covalent cross-links between protein-bound glutamine and protein-bound lysine residues, and (ii) cross-links between primary amines and protein-bound glutamine (Nurminskaya and Belkin, 2012).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 99%
“…PACAP is a pleiotropic molecule, involved in a wide range of physiological processes, including cell survival during neurodegenerative conditions, stress response and cell division (Canonico et al, ; Castorina et al, ; Castorina, Giunta, Mazzone, Cardile, & D'Agata, ; Castorina, Scuderi, D'Amico, Drago, & D'Agata, ; Cavallaro et al, , ; D'Agata & Cavallaro, ; D'Agata, Cavallaro, Stivala, Travali, & Canonico, ; D'Amico et al, , ; Giunta et al, ; Maino et al, ; Maugeri, D'Amico, & Gagliano, ; Maugeri, D'Amico, & Saccone, ; Scuderi et al, ). Moreover, it is known to act as a neurotransmitter and/or a neuromodulator in the peripheral and central nervous system (Jóźwiak‐Bębenista, Kowalczyk, & Nowak, ; Shioda et al, , ; Yang et al, ). Despite recent findings have revealed that PACAP is able to rescue rat motor neurons against glutamate‐induced excitotoxicity in vitro (Tomimatsu & Arakawa, ), and confers neuroprotection to central visceromotor neurons via autocrine pathways in SOD1(G93A) mice model (Ringer et al, ), the effect of PACAP in ALS still remains unknown.…”
Section: Introductionmentioning
confidence: 99%